Domestic, family and sexual violence in Australia: an overview of the issues - Janet Phillips
Provides an overview of research on the prevalence of domestic, family and sexual violence, at risk groups and the costs of violence against women to communities and to the economy. Introduction In 2013 the World Health Organization (WHO) published the first systematic international review on the prevalence of violence against women. During the course of the review the authors analysed and collated data from around the world, including Australia, on the prevalence of intimate partner violence and non-partner sexual violence. The review found that violence against women is a significant public health problem and a violation of human rights that affects more than one third of all women globally. The review concluded that the prevalence of violence constitutes ‘a global public health problem of epidemic proportions, requiring urgent action’. In Australia, domestic, family and sexual violence is widespread across all cultures, ages and socio-economic groups and the majority of those who experience these forms of violence are women. The most recent data on personal safety found that many men and women experience at least one encounter with violence in their lifetimes. The Australian Bureau of Statistics (ABS) survey estimated that in 2012, 49 per cent of men aged 18 years and over and 41 per cent of women aged 18 years and over had experienced some form of violence since the age of 15. Men were far more likely to experience physical violence at the hands of a stranger. However, the majority of women experienced physical violence by someone known to them—usually an intimate partner. While both men and women were more likely to experience physical violence than sexual violence, those who did experience sexual violence were much more likely to be women—around 4 per cent of men and 17 per cent of women had experienced sexual violence since the age of 15. Of those who experienced sexual violence (both men and women), the majority reported that the perpetrator was known to them. This research paper updates several previous Parliamentary Library publications on the levels of violence experienced by women in Australia. The paper includes an overview of research on the prevalence of domestic, family and sexual violence, at risk groups and the costs of violence against women to communities and to the economy. Limited comparisons of the levels of violence experienced by men and women are included where relevant. The paper also includes an overview of policy approaches designed to prevent violence against women